2008
DOI: 10.1124/jpet.108.143206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High and Low Folate Diets on Tissue Folate Receptor Levels and Antitumor Responses Toward Folate-Drug Conjugates

Abstract: Herein, we present a detailed analysis on the effects of feeding laboratory mice both high and low folic acid (folate)-containing diets as related to associated changes in serum and red blood cell (RBC) folate levels, tissue-derived folate receptor levels, and the ability of folate-drug conjugates to bind and effectuate activity against folate receptor (FR)-positive tumor xenografts. Our data show that serum and RBC folate concentrations sharply drop immediately after mice are switched to low folate diets; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 32 publications
3
57
0
1
Order By: Relevance
“…BALB/c mice have serum folate concentrations of approximately 250 nM, compared to 25 nM in humans (23). Therefore, mice were kept on a folate-deficient diet for 2 weeks prior to any treatments to bring down their serum folate to concentrations comparable to those in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BALB/c mice have serum folate concentrations of approximately 250 nM, compared to 25 nM in humans (23). Therefore, mice were kept on a folate-deficient diet for 2 weeks prior to any treatments to bring down their serum folate to concentrations comparable to those in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that high serum folate concentra-tions, like those found in the serum of laboratory rodents, could potentially block the binding of FA-drug conjugates to the folate receptors in tissues (22). Because of that, a mouse model treated with a folate-deficient diet was developed for the purpose of lowering endogenous mouse serum folate concentrations toward the normal human range (23). Therefore, in this study mice on both a folate-deficient diet and a normal diet were used.…”
mentioning
confidence: 99%
“…There were two distinct phases in erythrocyte folate kinetics; an initial phase lasting approximately 2 weeks during which erythrocyte folate concentration remained largely unchanged followed by exponential 'decay' in erythrocyte folate concentration towards a new equilibrium after 4-5 weeks (25) . For comparison, Leamon et al reported that erythrocyte folate reached a new (lower) plateau in BALB/c mice approximately 6 week after transfer to a low folate diet (27) . Further studies showed that a milder nutritional insult (feeding 0·4 mg folic acid/kg diet) reduced maternal and offspring erythrocyte folate concentrations (measured at weaning) by about 50 % (25) .…”
Section: Towards a Mouse Model For Testing The Effects Of Maternal Fomentioning
confidence: 99%
“…2B; ref. 26). KB cell (American Type Culture Collection; ATCC) integrity was confirmed (Genetica DNA Labs, Cincinnati, Ohio) with cells being 100% identical to reference cells from the ATCC.…”
Section: Synthesis Of Folate-vinblastine Conjugate (Ec0905) and Confimentioning
confidence: 99%
“…The in vivo activity and toxicity of EC0905 were determined in nu/nu mice (Balb/c-derived; Charles River, Wilmington, MA) fed a folate-free diet (Harlan diet #TD00434, Harlan Teklad, Madison, WI) to achieve serum folate concentrations similar to those in humans (26,27). EC0905 (2 mmol/kg) or vehicle control was administered intravenously 3 times per week for 2 weeks to mice with FR-positive KB xenografts, and tumor size and animal performance were monitored.…”
Section: Synthesis Of Folate-vinblastine Conjugate (Ec0905) and Confimentioning
confidence: 99%